Experimental study on strength of spot welded - Mohd Zaim, Din (2008)
In this research, the strength on the tensile-shear and coach peel type of welding joints in spot welding of 0.8 mm thicknesses mild steel sheets (JIS C314 SPCC-SD) was investigated. The welding joints were exposed to tensile shear and coach peel using tensile test machine, and the effect of welding time on coach peel strength and tensile shear strength was researched by using related period diagrams. A weld current period and weld time is 3 – 6 kA and 2 – 5 second respectively was selected during the welding process. In this experiment increasing welding times cause high heat input to weld zone and extending weld nugget, so the strength of joints increases mine while excessive heat energy input causes void and crack formations, partially spurt out of molten metal and so, the strength of joint decreases. The optimum parameter for tensile shear type is at 6 ampere (A) current and 4 second welds time (3847 N) and the highest strength for coach peel type is at 6 ampere current and 5 second welds time (889.5N). Finally the comparison result shown the higher strength of orientation using spot welding machine is tensile shear type.